Genetic damage in human peripheral lymphocytes exposed to antimicrobial endodontic agents - Da Silva, Glenda N.; De Camargo, Elaine A.; Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, Daniel A. (Elsevier B.V., 2007)
Objective. Formocresol, paramonochlorophenol, or calcium hydroxide have been widely used in dental practice to eradicate bacteria and consequently to produce root canal disinfection. Taking into consideration strong evidence for a relationship between DNA damage and carcinogenesis, the purpose of the present study was to evaluate the genotoxic effects of antimicrobial endodontic compounds in human peripheral lymphocytes by single-cell gel ( comet) assay. This technique detects DNA strand breaks in individual cells.Study design. A total of 10 mu L of the tested substance solution (formocreso1, paramonochlorofeno1, and calcium hydroxide at 100-mu g/mL concentration) was added to human peripheral lymphocytes from 10 volunteers for 1 hour at 37 degrees C. The negative control group was treated with vehicle control (PBS) for 1 hour at 37 degrees C, as well. For the positive control group, lymphocytes were exposed to hydrogen peroxide at 100 mu M during 5 minutes on ice.Results. No DNA breakage was detected after a treatment of peripheral lymphocytes by formocresol, paramonochlorophenol, or calcium hydroxide at 100 mu g/mL.Conclusions. In summary, our results indicate that exposure to formocresol, paramonochlorophenol, or calcium hydroxide may not be a factor that increases the level of DNA lesions in human peripheral lymphocytes as detected by single-cell gel (comet) assay.